18 months follow-up of deep molecular response 4.5 (MR4.5) with nilotinib in patients with newly diagnosed chronic-phase chronic myeloid leukemia: a prospective, multi-center study in China - Wen, Bingbing; Zhang, Yuming; Lin, Haiqing; Lou, Jin; Tu, Chuangqing; Jiang, Yirong; Liu, Xiaolian; Chen, Yan; He, Huiqing; Liu, Zelin; Xie, Xiaoling; Huang, Wangxiang; et al. (Frontiers in Medicine, 2023)
Introduction Early stable deep molecular response (DMR) to nilotinib is associated with goal of treatment-free remission (TFR) in patients with chronic-phase chronic myeloid leukemia (CML-CP). It is important to early distinguish between patients who can achieve a DMR and those who are fit for TFR. Methods We performed a multicenter study to explore the early cumulative MR4.5 rate at 18 months with nilotinib in patients with newly diagnosed CML-CP (ND-CML-CP) in China. Of the 29 institutes, 106 patients with ND-CML-CP received nilotinib (300 mg BID). Results and discussion The cumulative MR4.5 rate of nilotinib treatment at 18 months was 69.8% (74/106). The cumulative MMR and MR4.0 rates for nilotinib at 18 months were 94.3% (100/106) and 84.9% (90/106), respectively. Patients with an ultra-early molecular response (u-EMR) at 6 weeks were not significantly different in obtaining DMR or MMR by 24 months compared with those without u-EMR (p = 0.7584 and p = 0.9543, respectively). Our study demonstrated that nilotinib treatment in patients with ND-CML-CP contributed to obtain high early MR4.5.